PELAKSANAAN MODEL PERFORMANCE ASSESSMENT DALAM PEMBELAJARAN TAHSIN AL-QUR’AN DI PESANTREN DARUL MURSYIDI SIALOGO - hilmi HILMI (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2018)
Implementation of teaching and learning process is inseparable from the components of learning, one of the components of the learning that is the evaluation / assessment. Assessments that match the application of the 2013 curriculum are authentic assessments that refer to a scientific approach. Authentic assessment is done comprehensively and based on the process of learning activities demonstrated by learners during the learning which is called performance assessment (performance assessment). Pesantren Darul Mursyidi Sialogo one of the schools that apply the performance assessment model in the learning of Qur'anic tahsin. The advantage of learning tahsin in Pesantren Darul Mursyidi Sialogo by using performance assessment model is by demanding learners to do related tasks of learning, and direct educator to give assessment when the learning process takes place, it is held every meeting in class. Learning tahsin in Pesantren Darul Mursyidi Sialogo including extracurricular activities, and take place every Saturday is held once a week. The existence of tahsin learning by using performance assessment model can improve reading skill of al-Qur'an learners according to tajwid rule. This is obtained based on the Qur'an reading test and learners' learning outcomes, from 269 students there are 20 unfinished learners.Keywords: Performance Assessment Model, Learning Tahsin Al-Qur’an